Complement Receptors and Their Role in Leukocyte Recruitment and Phagocytosis - Vandendriessche, Sofie; Cambier, Seppe; Proost, Paul; Marques, Pedro E. (Frontiers in Cell and Developmental Biology, 2021)
The complement system is deeply embedded in our physiology and immunity. Complement activation generates a multitude of molecules that converge simultaneously on the opsonization of a target for phagocytosis and activation of the immune system via soluble anaphylatoxins. This response is used to control microorganisms and to remove dead cells, but also plays a major role in stimulating the adaptive immune response and the regeneration of injured tissues. Many of these effects inherently depend on complement receptors expressed on leukocytes and parenchymal cells, which, by recognizing complement-derived molecules, promote leukocyte recruitment, phagocytosis of microorganisms and clearance of immune complexes. Here, the plethora of information on the role of complement receptors will be reviewed, including an analysis of how this functionally and structurally diverse group of molecules acts jointly to exert the full extent of complement regulation of homeostasis.